2008
DOI: 10.1590/s0101-98802008000100016
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolipomatose do cólon: relato de caso

Abstract: RESUMO: A pseudolipomatose cólica é uma condição benigna, raramente descrita, caracterizada histologicamente pela presença de múltiplas vesículas contendo ar na parede do intestino grosso. Acredita-se que a doença tenha origem iatrogênica, ocasionada pela infiltração de ar através da mucosa cólica durante a realização de procedimentos endoscópicos. O objetivo do presente relato é apresentar um caso de pseudolipomatose cólica, confirmada por meio de estudo histopatológico e imunoistoquímico. Relato do caso: Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Weight loss is also an important sign. Martinez et al [46] reported a case of colon paracoccidioidomycosis in a 22-year-old man, who had lost 35 pounds in 5 months. Colonoscopy showed diffuse hyperemia of the mucosa and roundish reddened lesions, together with multiple ulcerations of the colon mucosa [46].…”
Section: The Chronic Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight loss is also an important sign. Martinez et al [46] reported a case of colon paracoccidioidomycosis in a 22-year-old man, who had lost 35 pounds in 5 months. Colonoscopy showed diffuse hyperemia of the mucosa and roundish reddened lesions, together with multiple ulcerations of the colon mucosa [46].…”
Section: The Chronic Formmentioning
confidence: 99%
“…Martinez et al [46] reported a case of colon paracoccidioidomycosis in a 22-year-old man, who had lost 35 pounds in 5 months. Colonoscopy showed diffuse hyperemia of the mucosa and roundish reddened lesions, together with multiple ulcerations of the colon mucosa [46]. Eventually, intestinal PCM may be confused with colon cancer, as reported by Chojniak et al [47], who described a case of an abdominal mass associated with intralesional calcifications in pseudotumoral PCM.…”
Section: The Chronic Formmentioning
confidence: 99%